Delayed luminescence of the H3 centre in diamond - Pereira, E.
The H3 centre in diamond is shown to present, besides the known prompt luminescence with a temperature independent decay time and quantum yield up to 500 K, a delayed luminescence identical to the prompt one, and a temperature dependent decay time of the order of a few milliseconds. The experimental results are interpreted as due to reversible non-radiative transitions from the emitting 1B1 excited level to triplet levels. Also upon excitation into the H13 absorption a delayed luminescence with a temperature independent decay of 1 ms indicates that de-excitation of H13 into the 1B1 level may proceed via an intermediate triplet level